TRAINER AND TRAINEES MODELING BASED ON COMPLEX INFORMATION APPROACH TO IMPROVEMENT OF TRAINING INFORMATION TECHNOLOGIES AND SYSTEMS - Khodakov, V. Ye.; Sokolov, A. Ye.; Veselovskaya, G. V. (Radio Electronics, Computer Science, Control, 2019)
Context. The problem in substantiation for methods on constructing models of trainer and trainees, taking into account the peculiarities of their information activity, is considered. The object for the study were the models of trainer and trainees as participants in information interaction. Objective. The goal for the work is the solving of the tasks in conceptualization and formalization, aimed at modeling the trainer’s subsystem in the framework of information technology for instruction, as well as modeling information flows and information procedures in the model of the trainee’s subsystem. Method. The key components of learning systems and processes are the trainer and trainees. The essential features of information interaction between the instructor and trainees are highlighted. The basis is the concept of the information flow, the specific properties of information flows that are characteristic of learning processes and important for their successful progress are identified. Methods for modeling the key components of the training system as an information system are proposed, such as: the trainer`s subsystem, considered from the point of view of the application for learning information technologies; a subsystem of the trainee, represented from the perspective of the use for information flows and information procedures. Results. The proposed models were implemented programmatically and studied practically in the learning processes as a result of working out the modeling tasks for the trainer and trainees as participants in information interaction. Conclusions. The conducted experiment confirmed the effectiveness and validity of the concepts and formalisms, the appropriateness for their implementation in information systems, processes and technologies of teaching with the purpose of increasing the processes efficiency on obtaining and practical implementation of information activity models for the trainer and trainees. Further development of research implies the consideration for a wider range of the information activity aspects on the educator and trainees, as well as the corresponding experimental approbations.